Instrumenty rachunkowości zarządczej w realizacji strategii projakościowej - Markowska, Małgorzata (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
Nowadays quality management is the base element in enterprise strategy. This article shows that it is possible to use in TQM the tools of management accounting like: the balanced scorecard, benchmarking and strategic cost management systems (quality costs accounting, target costing, product's life cycle costing, activity based costing). (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1080, s. 212-219